2020
DOI: 10.1155/2020/8586418
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Lymphocyte Ratio in Predicting Infective Endocarditis: A Case-Control Retrospective Study

Abstract: Background. Infective endocarditis (IE) is a complex infectious disease with high morbidity and mortality. The inflammation mechanism of IE is a complex network including interactions of inflammatory cytokines and other components of host response. As an important inflammation marker, the prediction ability of neutrophil-to-lymphocyte ratio (NLR) in IE deserves further investigation. Methods. NLR values were measured and compared between IE patients and healthy controls, good and bad clinical outcome groups. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In recent times, investigators have made a great effort to explore factors to judge the prognosis of patients with different diseases, such as IE [ 8 12 ]. LDH, lymphocyte, and LWR are inexpensive, easy to get, and automated factors that timely and effectively forecast the prognosis of the patients with different sicknesses [ 13 17 ]. Previous researches suggested that the performance (accuracy/precision) of the combination of LDH and lymphocyte (LDH/lymphocyte) was better than that of LDH and lymphocyte alone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, investigators have made a great effort to explore factors to judge the prognosis of patients with different diseases, such as IE [ 8 12 ]. LDH, lymphocyte, and LWR are inexpensive, easy to get, and automated factors that timely and effectively forecast the prognosis of the patients with different sicknesses [ 13 17 ]. Previous researches suggested that the performance (accuracy/precision) of the combination of LDH and lymphocyte (LDH/lymphocyte) was better than that of LDH and lymphocyte alone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with infective endocarditis have similarly higher stroke risk, 60 and are also thought to have higher baseline NLR due to the inflammatory nature of this condition. Higher baseline NLR is predictive for in‐hospital outcomes, 61 and may have a role in the risk stratification of patients 61 . However, a literature gap exists with NLR use in AIS patients with underlying infective endocarditis, with, to our knowledge, no studies in this group of patients, despite the higher stroke risk which infective endocarditis confers 60 …”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory factors, derived from lymphocyte, including platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and LWR, are eagerly connected with the clinical results of patients [ 17 ]. Some studies suggested that lymphocyte and its related index, such as platelet-to-lymphocyte ratio (PLR) and neutrophil-lymphocyte ratio (NLR), were associated with the diagnosis and prognosis of IE [ 11 , 12 ]. Our work also found that lymphocyte count was lower in the nonsurvivor group compared with the survivor group, while it was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, a sole index could not truly reflect all possible conditions of patients. Recently, some studies tried to analyze the value of comprehensive indexes, such as lymphocyte and its related index in predicting prognosis of IE [ 11 , 12 ], while the association of lymphocyte-to-white blood cell ratio (LWR) with short-term mortality in IE patients remains unknown. Therefore, we conducted this investigation to evaluate the value of admission LWR for prediction of short-term mortality in IE patients.…”
Section: Introductionmentioning
confidence: 99%